Obtención de butanol a partir de bagazo de malta (2024)
The objective of this research is to evaluate the biobutanol production process using malt bagasse as a carbon source, in order to develop a strategy to improve the management of lignocellulosic waste. To achieve this objective, laboratory-scale experiments were carried out that included acid hydrolysis of malt bagasse to release fermentable sugars and its subsequent anaerobic fermentation using the bacterium Clostridium acetobutylicum. The methodology consisted of: physical pretreatment of the bagasse, acid hydrolysis to obtain sugars, quantification of sugars in the hydrolysate, preparation of the fermentation medium, inoculation and fermentation and, finally, a pilot-scale conceptual design of the biobutanol production process is proposed.